1990
DOI: 10.1104/pp.92.3.747
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of the Red Beet Plasma Membrane Ca2+-ATPase Using GTP as an Alternative Substrate

Abstract: The GTP-driven component of Ca2+ uptake in red beet (Beta vulgaris L.) plasma membrane vesicles was further characterized to confirm its association with the plasma membrane Ca2+-trans-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
56
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 29 publications
7
56
1
Order By: Relevance
“…These data are consistent with the lack of a calmodulin binding domain in the deduced LCA amino acid sequence (Wimmers et al, 1992). In previous studies, calmodulin sensitivity was reported for the PM Ca2+-ATPases from maize (Robinson et al, 1988;Briars and Evans, 1989), red beet roots (Williams et al, 1990), carrot cell cultures (Hsieh et al, 1991), and radish seedlings (Rasi-Caldogno et al, 1992. In contrast, calmodulin had no effect on the PM Ca2+-ATPases from pea roots (Butcher and Evans, 1987) and Commelina communis leaves (Siebers et al, 1990).…”
Section: )supporting
confidence: 73%
“…These data are consistent with the lack of a calmodulin binding domain in the deduced LCA amino acid sequence (Wimmers et al, 1992). In previous studies, calmodulin sensitivity was reported for the PM Ca2+-ATPases from maize (Robinson et al, 1988;Briars and Evans, 1989), red beet roots (Williams et al, 1990), carrot cell cultures (Hsieh et al, 1991), and radish seedlings (Rasi-Caldogno et al, 1992. In contrast, calmodulin had no effect on the PM Ca2+-ATPases from pea roots (Butcher and Evans, 1987) and Commelina communis leaves (Siebers et al, 1990).…”
Section: )supporting
confidence: 73%
“…Vol. 108, 1995 fairly similar biochemical characteristics and their reported values of molecular mass fall in the same range (Evans et al, 1989;Williams et al, 1990;Hsieh et al, 1991;Askrdund andEvans, 1992, 1993;Chen et al, 1993;Thomson et al, 1993Thomson et al, , 1994; therefore, they are not easily discerned.…”
mentioning
confidence: 91%
“…In fact, it is half-saturated by Ca2+ in the micromolar range and has a very high affinity for MgATP (Rasi-Caldogno et al, 1989;Carnelli et al, 1992;De Michelis et al, 1992. Finally, the PM Ca2+-ATPase activity is regulated by CaM, which strongly increases the V,,, of the reaction, thus making the enzyme up-regulated by an increase of cytosolic Ca2+ and Ca2+-CaM concentrations (Malatialy et al, 1988;Robinson et al, 1988;Williams et al, 1990;Erdei and Matsumoto, 1991;Carnelli et al, 1992;Rasi-Caldogno et al, 1992;De Michelis et al, 1993).…”
mentioning
confidence: 99%
See 2 more Smart Citations